Резонансный измерительный преобразователь в схеме резонатора бегущей волны с активным элементом - Бондаренко, И. Н.; Васильев, Ю. С.; Ткаченко, О. Н. (ХНУРЭ, 2009)
Characteristics waveguide traveling-wave resonators are considered and analysed at inclusion in their ring circuit of such elements as resonant measuring converters with different brought losses, narrow band and broadband amplifiers with different gain and bands of gain frequencies. Possibilities of indemnification of the losses brought by resonant converters are estimated, at preservation of their appreciable influence on AFC TWR with active elements. The carried out researches prove possibility of creation on the basis of ATWR the devices, allowing to compensate the static losses brought in RMC investigated sample or a sensitive element, at preservation and sensitivity increase to changes of measured sizes.
Keywords: измерительный преобразователь; резонатор бегущей волны